EMG activity of trunk stabilizer muscles during Centering Principle of Pilates Method - Marques, Nise Ribeiro [UNESP]; Morcelli, Mary Hellen [UNESP]; Hallal, Camilla Zamfolini [UNESP]; Gonçalves, Mauro [UNESP] (My University, 2013)
This study aimed to analyze the electromyographic (EMG) activity of iliocostalis lumborum (IL), internal oblique (IO) and multifidus (MU) and the antagonist cocontraction (IO/MU and IO/IL) during the performance of Centering Principle of Pilates Method. Participating in this study were eighteen young and physically fit volunteers, without experience in Pilates Method, divided in two groups: low back pain group (LBPG, n = 8) and control group (CG, n = 10). Two isometric contractions of IO muscles (Centering Principle) were performed in upright sitting posture. EMG signal amplitude was calculated by Root Mean Square (RMS), which was normalized by RMS maximum value. The common area method to calculate the antagonist cocontraction index was used. MU and IO activation and IO/MU cocontraction (. p < 0.05) were higher in CG. The CG therefore showed a higher stabilizer muscles recruitment than LBPG during the performance of Centering Principle of Pilates Method. © 2012 Elsevier Ltd.
Keywords: Electromyographic; Low back pain; Pilates Method; adult; antagonist cocontraction; controlled study; electromyogram; female; human; iliocostalis lumborum muscle; internal oblique muscle; low back pain; multifidus muscle; muscle contraction; muscle isometric contraction; pilates; sitting; skeletal muscle